1997
DOI: 10.1002/(sici)1097-461x(1997)63:3<729::aid-qua14>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Semiempirical calculations on WO 3 and M X WO 3 crystals (M = H, Li, Na)

Abstract: ABSTRACT:The monoclinic structure of tungsten trioxide WO has been studied by 3 Ž . combining a modified intermediate neglect of differential overlap INDO method and the supercell model. The fitted semiempirical parameters describe very well the features of the band structure and crystal structure. Calculations of H, Li, and Na impurities in a WO crystal have been performed to study the absorption spectra and the equilibrium 3 geometries of intercalated impurities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Most band structure calculations have considered crystalline WO 3 . [21][22][23][24] Recently, a calculation for amorphous WO 3 has also appeared. 25 This indicates that the amorphous structure leads to localizations of the lower part of the conduction band.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Most band structure calculations have considered crystalline WO 3 . [21][22][23][24] Recently, a calculation for amorphous WO 3 has also appeared. 25 This indicates that the amorphous structure leads to localizations of the lower part of the conduction band.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Deb's vacancy model [1] suggests that the oxygen vacancy (V O ) is involved in the optical transition; while all the other models suggest that the optical transition occurs via the charge transfer between non-equivalent W sites in one way or the other [4 -6]. It is found in Ref.[7] that the electrochromic colouration efficiency and conductivity is enhanced, and the peak energy of the mid-gap absorption shifts to the higher energy, with increasing oxygen deficiency.There have been numerous theoretical studies on the electronic structure of WO 3 with and without ion intercalation: non-self-consistent and/or semi-empirical calculations [8][9][10][11], and self-consistent first-principles calculations [12 -16]. However, no publications on the theoretical study of V O in WO 3 system either with or without the intercalation have been found except for one for amorphous WO 3 [17].…”
mentioning
confidence: 99%
“…There have been numerous theoretical studies on the electronic structure of WO 3 with and without ion intercalation: non-self-consistent and/or semi-empirical calculations [8][9][10][11], and self-consistent first-principles calculations [12 -16]. However, no publications on the theoretical study of V O in WO 3 system either with or without the intercalation have been found except for one for amorphous WO 3 [17].…”
mentioning
confidence: 99%
“…It is important to note that the relativistic effects for the Pb atom were indirectly taken into account by reproducing the PbTiO 3 crystal band structure properties [26]. This was accomplished, as previously published for the W atom [31], by manipulating the atomic parameters and incorporating special pseudopotentials into our computer code [32]. An important feature of these pseudopotentials is that relativistic effects are included that also enable them to be used in nonrelativistic formulations.…”
Section: Outline Of the Computational Methodsmentioning
confidence: 99%